The Effect of Plant Distance on the Growth and Production of Sticky Corn (Zea Mays Ceratina L.) - Abdul Wachid; Eko Khuluk Andi Lesmana (Nabatia, 2020)
Glutinous corn or waxy corn or glutinous corn (Zea mays ceratina. L) is a special type of corn that has the potential as a source of diversification of food and industrial materials. Glutinous corn is a source of germplasm to become new cultivars through plant breeding. This study aims to determine the effect of spacing on the growth and production of glutinous corn (Zea mays ceratina L.). This research was carried out in the farmers’ land of Jiken Village, Tulangan Subdistrict, Sidoarjo Regency. With a height of ± 7 meters above sea level, Ph 6.5 and a temperature of 25-27 ° C. The study was conducted from February to April 2020. This study used a single Randomized Group Design (RCBD), with a plant spacing factor: spacing factor 40 x 15 cm, spacing factor 40 x 20 cm, spacing factor 40 x 25 cm, spacing factor 40 x 30 cm and spacing factor 40 x 35 cm. From these factors, 5 treatments were obtained and repeated 4 times so that 20 experimental units were obtained. The results of this study indicate the effect of spacing on the growth and production of glutinous corn, on the spacing of planting spacing, it shows that spacing can increase Plant Height, number of seed consoles, number of row row, number of seeds perongkol, length of planting cobs and diameter of planting cobs.